In vitro assembly of a viral envelope. Issue 39 (21st October 2015) - Miles, Penny; Cassidy, Peter; Donlon, Lynn; Yarkoni, Orr; Frankel, Daniel
<x xml:space="preserve">Abstract</x> HIV glycoproteins distort lipid vesicles suggesting a capsid is necessary for virion stability these glycoproteins can also assemble into molecular wires.